2007
DOI: 10.1017/s0022112007007550
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent flow on a planar moving belt and a rotating disk: modelling and comparisons

Abstract: Modelling of the fully turbulent flow produced on a moving belt and of that induced on a rotating disk is described, for each of which a more analytical approach is adopted than previously seen. The analysis for the two-dimensional moving belt indicates novel structures and these are found to carry over directly to the rotating disk flow which, ignoring the transitional regime, is three-componential but twodimensional due to axisymmetry. This is based on addressing the Reynolds-averaged Navier-Stokes equations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
25
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(29 citation statements)
references
References 31 publications
4
25
0
Order By: Relevance
“…The simpler case of the turbulent boundary layer on a rotating disk was examined in [10] where it was found that the boundary layer is relatively massive, a result also reported in [11] concerning turbulent jets and [12] concerning marginal separation. In this paper we extend the work of [10] to include non-axisymmetry by considering the fully three-dimensional turbulent boundary layer (cf.…”
Section: Introductionmentioning
confidence: 75%
See 4 more Smart Citations
“…The simpler case of the turbulent boundary layer on a rotating disk was examined in [10] where it was found that the boundary layer is relatively massive, a result also reported in [11] concerning turbulent jets and [12] concerning marginal separation. In this paper we extend the work of [10] to include non-axisymmetry by considering the fully three-dimensional turbulent boundary layer (cf.…”
Section: Introductionmentioning
confidence: 75%
“…The fluid motion induced is usually turbulent in practice. For example, one motivation for the current theoretical work is from industry, where the possible application to rotor-blade flows represents a potentially significant area of research not least because of its use in the study of helicopter dynamics and the desire within industry to develop a theoretical understanding of such flows in the hope that this may lead to improvements in design [1][2][3][4][5][6][7][8][9][10]. The detailed link with the present work may be quite indirect throughout as our emphasis is on fundamental properties and asymptotic description; indeed, the apparent breaks of both symmetry and periodicity associated with forward movement (rather than hovering) of a helicopter and the resulting complex vortex streets are not addressed.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations